The dynamics of vegetation of lower reaches water of the Sula river (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
The dynamics of vegetation water, the lower reaches river Sula was analyzed. Research territory for the administrative division of Ukraine belongs to the southwestern part of Poltava and northeastern regions of Cherkassy. It was established that for waters of the lower reaches of Sula river are characterized by autogenetic (syngenetic, endogenetic) and ekzoekogenetic (natural and anthropogenic) changes. The main directions and trends in vegetation were described. Generalized scheme of water vegetation changes depending on the type of bottom sediments, water column, and the flow velocity was given.
Keywords: dynamics, vegetation water, autogenesis, ekzoekohenez, lower reaches of the district river Sula.